Venous Thrombotic, Thromboembolic, and Mechanical Complications After Retrievable Inferior Vena Cava Filters for Major Trauma. Issue 6 (December 2016) - Ho, K. M.; Tan, J. A.; Burrell, M.; Rao, S.; Misur, P.
Abstract : (Abstracted from Br J Anaesth, 114:63–69, 2015) Venous thromboembolism (VTE) is common in critically ill patients, and thromboprophylaxis is proven to be crucial in reducing mortality and morbidity from VTE. Permanent and retrievable inferior vena cava (IVC) filters are frequently used for thromboprophylaxis.